Analysis of ways action troop groups under deleting illegal armed groups - Lavnichenko, О. V.; Varakuta, V. P.; Luhovskyi, І. S.; Kryvenko, О. V. (Honor and Law, 2019)
Modern ways action state troop groups on deleting illegal armed groups are analyzed. Principles of the choice these forms and ways on criterion of their practicability as final result and redistributions function between troop armed groups during execution special operation in internal armed conflict are offered.